2019
DOI: 10.3389/fpls.2019.01397
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Theanine Accumulation and Related Gene Expression in the Roots and Leaf Buds of Tea Plants (Camellia Sinensis L.)

Abstract: Theanine, a unique and abundant non-proteinogenic amino acid in tea, confers to the tea infusion its umami taste and multiple health benefits. Its content in new tea shoots is dynamic in winter and spring. However, its seasonal accumulation pattern and the underlying regulation mechanism of tea plants remain largely unknown. In this study, we measured the theanine contents in the roots and leaf buds of 13 tea cultivars at four time points from winter to spring (Dec. 12, Mar. 1, Mar. 23, and Apr. 13). We found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 61 publications
1
38
0
1
Order By: Relevance
“…For example, Huang et al reported that supplying tea plants with different forms of N significantly increase Pro, Glu, and Thea in tea leaves compared with 0 N, especially when supplied with NH 4 + -N 58 , whereas they did not examined amino acid contents changes in tea plant root. Actually, previous studies reported that many amino acids are mainly synthesized in tea root, and are then transported from root to shoot 41,44,45 ) treatments for 5 min and 96 h on gene expression, but they mixed root, stem, leaf and shoot samples together for the analysis. Thus, the tissue-specific response of gene expression could not be elucidated 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Huang et al reported that supplying tea plants with different forms of N significantly increase Pro, Glu, and Thea in tea leaves compared with 0 N, especially when supplied with NH 4 + -N 58 , whereas they did not examined amino acid contents changes in tea plant root. Actually, previous studies reported that many amino acids are mainly synthesized in tea root, and are then transported from root to shoot 41,44,45 ) treatments for 5 min and 96 h on gene expression, but they mixed root, stem, leaf and shoot samples together for the analysis. Thus, the tissue-specific response of gene expression could not be elucidated 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Until now, the gene encoding for theanine hydrolase has not been identified yet. Finally, it is noteworthy that Thea is mainly synthesized in roots and is transported through the vascular system to tea plant shoots [41][42][43][44][45] .…”
mentioning
confidence: 99%
“…AATs might be involved in the homeostasis of AAs and in their sequestration in organelles; thus, their expression patterns may affect tea taste quality [ 33 , 35 ]. The expression of AATs involved in soil-to-root (uptake) would depend on AA recognition as substrates and AA availability.…”
Section: Discussionmentioning
confidence: 99%
“…In the mature tea plant, theanine biosynthesis mostly occurs in roots [ 32 ], from where it is transported via the phloem, after loading by transporters, through stems to young buds and leaves. Therefore, amino acid transporters (AATs) in tea plants have received much attention in recent years [ 33 , 34 , 35 ]. Physiological functions of transporters, mediating N transmembrane transport from the soil into roots, from roots to shoots, and remobilization within the tea plant, should be investigated to highlight the importance of different transport systems and to reveal different AA behavior patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Iz rezultata dobijenih u ovom radu (tabela 2) može se uočiti da je sadržaj kofeina u ispitivanim uzorcima uglavnom u okviru prosečnih vrednosti za ove vrste čajeva (sa izuzetkom uzoraka ZČ1), ali ove vrednosti međusobno variraju, što može biti posledica više različitih faktora kao što su: geografsko poreklo, klimatski uslovi, uslovi gajenja, različiti fenotipovi iste biljke, korišćenje različitih fitohemikalija, sezona berbe (proleće, leto ili jesen). Važni faktori svakako jesu i uslovi sušenja, skladištenja i čuvanja, ali i pripreme čaja (28,(30)(31)(32)(33)(34)(35).…”
Section: Diskusijaunclassified